Manejo de densidad en rodales de pochote (Bombacopsis quinata (Jacq) Dugand) en las tierras bajas de Costa Rica (ING) - Chinchilla Mora, Orlando; Chaves Salas, Eladio (Uniciencia, 1990)
Results are presented on response of B.quinata (Jacq) Dugand to different thinning intensities, for a five year period of observation in two sites in Costa Rica. Two thinnings were done at the Nicoya plantation; the first one when trees were five years old (17.8 m2/ha) and the second two years later, when the control plots had 24.8 m2/ha in basal area. The first thinning was done before time because the plot had not reached a limiting basal area. Therefore no significant differences in diameter and height increment between treatments were found. However significant differences in basal area increment were found. For the 1986-88 period the treatment effects resulted in highly significant diameter and basal area increments, but not for height increments. In the Santa Cruz plantation only one thinning was done when trees were six years old and the average basal area was 18.05 m2/ha. For the period 1985-88 treatment effect showed significant increments in diameter and basal area, but not height increments. While for the period 1986-88 the treatments showed no significant effect in diameter and height increments. The stocking influenced the diameter and basal area between 22 m2/ha and 25 m2 /ha. With this evidence at hand, we suggest that the first thinning should be done when the basal area reaches the sizes mentioned above, and between 6-8 m2/ha should be removed to get a good plantation development. The recommendation applies for the second thinning.